Pengaruh Kepemimpinan Transformasional dan Budaya Organisasi Terhadap Kinerja Karyawan - Ahmad Rivai (Maneggio: Jurnal Ilmiah Magister Manajemen, 2020)
The purpose of this study was to determine and analyze the effect of transformational leadership on employee performance at PT Federal International Finance - Medan, to determine and analyze the influence of organizational culture on employee performance at PT Federal International Finance - Medan and to determine and analyze the influence of transformational leadership and organizational culture. on employee performance at PT Federal International Finance - Medan. The population of this study were all 60 permanent employees of PT Federal International Finance-Medan. The data analysis technique used is multiple regression. The results of this study indicate that partially transformational leadership and organizational culture have a positive and significant effect on the performance of employees of PT Federal International Finance - Medan and that transformational leadership and organizational culture simultaneously have a positive and significant effect on the performance of employees of PT Federal International Finance – Medan.